2021
DOI: 10.3390/jcm10040795
|View full text |Cite
|
Sign up to set email alerts
|

Screen Time and Parents’ Education Level Are Associated with Poor Adherence to the Mediterranean Diet in Spanish Children and Adolescents: The PASOS Study

Abstract: The aim of this study is to evaluate if screen time and parents’ education levels are associated with adherence to a Mediterranean dietary pattern. This cross-sectional study analyzed a representative sample of 3333 children and adolescents (8 to 16 years) included in the Physical Activity, Sedentarism, lifestyles and Obesity in Spanish youth (PASOS) study in Spain (which ran from March 2019 to February 2020). Data on screen time (television, computer, video games, and mobile phone) per day, Mediterranean diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 68 publications
2
32
0
4
Order By: Relevance
“…Likewise, in the present study, low educational level (primary/secondary level) reported in the parents of Chilean children showed a positive association with ST of more than 4 h a day. A recent study reported that daily ST was significantly lower in children whose parents had higher education levels (i.e., university education) compared with peers whose parents had a secondary or primary, or no formal education [ 52 ]. Moreover, Määttä et al [ 40 ] indicated that parents with a high education judged it to be of greater importance to limit the ST of preschool children, compared to parents with low education.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in the present study, low educational level (primary/secondary level) reported in the parents of Chilean children showed a positive association with ST of more than 4 h a day. A recent study reported that daily ST was significantly lower in children whose parents had higher education levels (i.e., university education) compared with peers whose parents had a secondary or primary, or no formal education [ 52 ]. Moreover, Määttä et al [ 40 ] indicated that parents with a high education judged it to be of greater importance to limit the ST of preschool children, compared to parents with low education.…”
Section: Discussionmentioning
confidence: 99%
“…It should be indicated that increased screen time, which is commonly observed during the COVID-19 pandemic [68], may also be an important factor influencing food habits. A study conducted in a Spanish population of children and adolescents during the COVID-19 pandemic revealed that increased screen time was associated with worse dietary behaviors, including lower intake of fruit, vegetables, fish, pulses, and nuts, but higher intake of fast foods and sweets [69]. Similar observations of increased screen time have also been indicated during the COVID-19 pandemic in the population of Polish adolescents [2].…”
Section: Discussionmentioning
confidence: 62%
“…Additionally, excessive screen time has been associated with higher energy intake, lower consumption of fruits and vegetables, higher consumption of saturated fat, and lower quality of nutrients, suggesting that screen time leads to higher intake caloric associated with junk food, which could be influenced by watching food advertisements during TV viewing [52,53].…”
Section: Academic Achievementmentioning
confidence: 99%